Raman spectroscopy analysis of DNA using the SERS method - Varela-Fonseca, Stephanie (2019)
The technological advances of the last decades have contributed to the development of new methodologies for the characterization of biological samples. Raman Spectroscopy has been used for the characterization of pure inorganic and organic compounds, but recently, it is being used to study molecular structures of biological importance. Fluorescence is usually present in Raman spectroscopy, shielding Raman signals, but using the SERS (Surface Enhanced Raman Spectroscopy) technique, it is possible to locally increase the Raman signal and to reduce the importance of the fluorescence effects on the samples. The SERS effect could be achieved by adding metallic nanoparticles, of a specific size distribution, to the sample. Usually gold and silver nanoparticles are used for SERS. In this research, DNA of human and Rickettsia bacteria were characterized by the SERS technique, with both silver and gold nanoparticles.